METHODOLOGY FOR SIMPLIFYING THE ZHEGALKIN POLYNOMIAL IN BOOLEAN ALGEBRA (Modern American Journal of Engineering, Technology, and Innovation, 2026)
This article discusses the mathematical essence of the Zhegalkin polynomial in logical algebra and the methodology for simplifying expressions through specific examples in the process of teaching the subject "Discrete Structures" to students of the "Artificial Intelligence" educational program in technical higher education institutions.